Do Chest Compresses with Mustard or Ginger Affect Warmth Regulation in Healthy Adults? A Randomized Controlled Trial. (18th July 2022) - Vagedes, Jan; Kuderer, Silja; Vagedes, Katrin; Szőke, Henrik; Kohl, Matthias; Joos, Stefanie; Beissner, Florian; Wolf, Ursula
Abstract : Background . Chest compresses with mustard (MU) or ginger (GI) are a complementary treatment option for respiratory tract infections. However, little is known about their specific thermogenic qualities. This study examines the short-term effects of MU, GI, and chest compresses with warm water only (WA) on measurable and self-perceived body warmth in healthy adults. Methods . This was a single-center, randomized controlled trial with cross-over design (WA versus MU versus GI). 18 participants (23.7 ± 3.4 years; 66.7% female) received MU, GI, and WA in a random order on three different days with a mean washout period of 13.9 days. Chest compresses were applied to the thoracic back for a maximum of 20 minutes. The primary outcome measure was skin temperature of the posterior trunk (measured by infrared thermography) immediately following removal of the compresses (t1). Secondary outcome measures included skin temperature of the posterior trunk 10 minutes later (t2) and several parameters of self-perceived warmth at t1 and t2 (assessed with the Herdecke Warmth Perception Questionnaire). Results . Skin temperature of the posterior trunk was significantly higher with MU compared to WA and GI at t1 (p  < 0.001 for both, primary outcome measure) and t2 (WA versus MU: p = 0.04, MU versus GI: p < 0.01 ). Self-perceived warmth of the posterior trunk was higher with MU and GI compared to WA at t1 (1.40 ≥  d  ≥ 1.79) and remained higher with GI at t2 (WA versus GI: d  = 0.74). The overall warmth perception increased significantly with GI ( d  = 0.69), tended to increase with MU ( d  = 0.54), and did not change with WA ( d  = 0.36) between t0 and t1. Conclusions . Different effects on warmth regulation were observed when ginger and mustard were applied as chest compresses. Both substances induced self-perceived warming of the posterior trunk, but measurable skin temperature increased only with MU. Further research is needed to examine the duration of these thermogenic effects and how chest compresses with ginger or mustard might be incorporated into practice to influence clinical outcomes in respiratory tract infections.